Estudo do worldness da media franchising de Harry Potter - Andrade, Carolina Lourenço Reimberg de (2018)
The Harry Potter saga, created by the British J.K. Rowling is among the most successful film franchise works, that even after the end of the original book series and its cinematographic adaptations, continues to spread and expand to other areas of entertainment. The objective of this research is to analyze the narrative structure of the eight films of the Harry Potter saga (2001-2011) and the film of the same worldness Fantastic Beasts and Where to Find Them (2016), following the proposal of Vogler (2015) to understand the relation between one and another and the narratives components that collaborate with the spread of the franchise using the proposal of Derek Johnson (2013) on media franchise.